Activating the desire to learn - Sullo, Robert A., 1951- (Alexandria, Va. : Association for Supervision and Curriculum Development, 2007)
Discusses how to apply lessons from the research on motivation in the classroom, from elementary through high school.
Acknowledgments -- Introduction -- pt. 1. Theory and research -- ch. 1. Understanding internal motivation -- ch. 2. "Where's the evidence?" -- pt. 2. Elementary school -- ch. 3. Competition is as important as cooperation -- ch. 4. Helping students value learning -- ch. 5. From bossing to leading -- ch. 6. "Consequence" is not a four-letter word -- pt. 3. Middle school -- ch. 7. Positive relationships support competence and high standards -- ch. 8. Self-evaluation leads to lasting change -- ch. 9. Inspiring through collaboration -- ch. 10. Being what we choose -- pt. 4. High school -- ch. 11. Creating a need-satisfying environment -- ch. 12. From telling to asking -- ch. 13. From enforcing to teaching responsibility and fostering positive relationships -- ch. 14. Reflections of a high school senior -- Final thoughts -- Bibliography -- Index -- About the author.
Includes bibliographical references (p. 158-160) and index.
Keywords: Motivation in education; Learning; Motivation (Psychology); Achievement motivation in adolescence; Effective teaching